Kontribusi Kepemimpinan dan Kompensasi dalam Meningkatkan Kinerja melalui Motivasi Kerja Karyawan - Desianti Desianti; Rabihatun Idris; Muklis Kanto; Munandar Munandar (JMK (Jurnal Manajemen dan Kewirausahaan), 2021)
Exploration of the antecedents of performance with the support of good leadership and compensation as well as the support of high work motivation is the purpose of this study. The quantitative paradigm is an approach in this study that seeks to explore the triggers for high performance, the population in this study is the entire employee at Pt Bank Sulselbar in Makassar as many as 256 people, the sampling technique uses a simple random sampling method with a total sample of 156 people. The analysis used in testing the hypothesis is Structural Equation Modeling (SEM) with the help of WarpPLS Software version, 6.0. The results of this analysis show that there is a direct relationship between leadership constructs that have an influence on performance, compensation also has a direct influence on performance and motivation has a direct influence on performance variables, leadership directly has a direct relationship to performance and compensation also has a positive effect on motivation, Leadership indirectly affects performance through motivation as a mediator, motivation cannot mediate between the relationship between leadership and performance.